Problems and disadvantages of the existing evaluation system of thermomodernization projects of construction objects - Vahovich І.V.; Maximov, A.S.; Ostapenko І.О.; Bogatyuk, D.V.; Kalashnikov, D.P. (Ways to Improve Construction Efficiency, 2021)
The article considers the topical issue of thermal modernization of residential buildings and social facilities is an important area of research, but in the implementation of such projects there are many obstacles of organizational and administrative nature, which currently hinder the implementation of projects to improve energy efficiency of buildings and structures. and the systematization of which will allow to develop measures to eliminate existing barriers, and thus improve the attractiveness and accessibility of thermal modernization projects for the population and other stakeholders. The main stages of thermal modernization are systematized in accordance with the provisions of the current legislative and regulatory framework, the place of thermal modernization measures in the sequence of implementation of investment and construction projects is determined. It is determined that the main types of construction in which thermal modernization is carried out are capital repairs, reconstruction and technical re-equipment, but thermal modernization measures can be carried out during the current repair. Current repairs are not a type of construction, and therefore it is not subject to laws and regulations in the field of construction, and therefore the organization and implementation of such works from the standpoint of the requirements of legislation and regulations is the simplest. The following obstacles and barriers were identified during the development of the thermal modernization project, namely: the order of performance of the technical condition survey and energy audit is not legally established (in practice these are two unrelated actions, the result of which are not related technical reports analyzed by the designer. design), the stages of thermal modernization are not linked to a single methodology, given in separate documents, and therefore require special professional knowledge, not sufficiently reflected stages of preparation of thermal modernization at the stage of pre-design work, while at this stage decisions must be made , providing the required level of energy efficiency for the customer, technical and economic indicators of the project.